Modeling the relationship of research university brand image on students’ satisfaction and its effect on brand loyalty / Noordini Abdullah - Abdullah, Noordini (Institute of Graduate Studies, UiTM, 2016)
The role of universities in attracting postgraduate students to achieve a research university status has attracted the attention of scholars. While there is growing consensus that branding and internationalization is important, the relationship between a university’s research status, its strategy and its ability to attract postgraduate students is still unclear. Furthermore, on closer inspection, empirical studies that assess the impact of both brand image and students’ satisfaction on postgraduates’ brand/institution loyalty are lacking. Hence, this study aims to address this knowledge gap and attempts to extend previous studies on brand image by integrating satisfaction constructs into the framework. The main objective of this research is to develop a model of Research University brand image which is capable of delivering students’ satisfaction and loyalty. In addition, this research examined and identifies key dimensions or indicators and analyse the perspectives of postgraduate students on the dimensions and indicators necessary to evaluate Research University brand image…